2022
DOI: 10.2147/dmso.s343374
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Triglyceride-Glucose Index and 2-Year Adverse Cardiovascular and Cerebrovascular Events in Patients with Type 2 Diabetes Mellitus Who Underwent Off-Pump Coronary Artery Bypass Grafting

Abstract: Background: Data on the relationship between the triglyceride glucose (TyG) index and prognosis after off-pump coronary artery bypass grafting (OPCABG) are limited. This retrospective observational cohort study evaluated the association of the TyG index with prognosis in patients with diabetes mellitus who underwent OPCABG. Methods: The TyG index was calculated using the following equation: TyG index = ln (fasting triglyceride level [mg/dL] × fasting glucose level [mg/dL]/2). The primary outcomes included the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…In this regard, the TyG index exhibited great potential as a cardiovascular risk predictor [ 15 17 , 37 , 38 ]. In the present study, we confirmed again that the TyG index was independently associated with MACE in patients who underwent CABG, consistent with previous findings in patients with DM [ 18 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this regard, the TyG index exhibited great potential as a cardiovascular risk predictor [ 15 17 , 37 , 38 ]. In the present study, we confirmed again that the TyG index was independently associated with MACE in patients who underwent CABG, consistent with previous findings in patients with DM [ 18 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among patients after revascularization, those with high levels of TyG index usually had poor prognosis [ 15 17 ]. Chen et al found that the TyG index was an independent prognostic factor in diabetic patients after CABG [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tai et al showed that a higher levels of TyG index were significantly associated with an increased risk of major adverse cardiovascular events in patients with T2DM during 10 years follow-up [ 23 ]. A single-center, observational, retrospective cohort study including 1578 asymptomatic subjects with T2DM who underwent off-pump coronary artery bypass grafting (OPCABG) showed that TyG index may be a valuable predictor of adverse cardiovascular and cerebrovascular outcomes after OPCABG in patients with T2DM [ 24 ]. These studies suggested that TyG index can be a reliable predictor to predict the prognosis of cardiovascular and cerebrovascular related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In total, our study evaluated 4,405 relevant articles that were initially screened from electronic databases, but only 28 articles met our inclusion criteria, which contained a total of 11,944,688 participants. These 28 studies, involving nineteen cohort studies [10,19,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and ten case-control/cross-sectional studies [16,18,38,[44][45][46][47][48][49][50] (with one of the articles including both cohort and cross-sectional portions), investigated the risk of cerebrovascular disease in populations with different TyG index. The specific details are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%